ANALISIS HUKUM TINDAK PIDANA CYBER DATA BREACH DI ERA DIGITAL BERDASARKAN UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK (STUDI PUTUSAN NOMOR 2447/PID.SUS/2024/PN MDN) - Silvana Silalahi, Ririn; Mulyadi, Mahmud; Trisna, Wessy (Penerbit Lafadz Jaya, 2025)
The rapid development of information technology has brought convenience to people's lives but also presents new challenges in the form of cybercrime, particularly Cyber Data breach which has serious impacts on personal data protection and individual privacy rights. Specifically, this research analyzes Cyber Data breach crimes from the perspective of Indonesian criminal law using normative juridical methods with statutory and case study approaches to Decision Number 2447/Pid.Sus/2024/PN Mdn, which shows that legal regulations regarding Cyber Data breach are still general and scattered across various regulations, especially the ITE Law and PDP Law, thus requiring crucial integration between these two laws so that prevention can be carried out comprehensively from both preventive and repressive aspects, where the panel of judges has applied the provisions of the ITE Law normatively and proportionally by using Article 30 paragraph (3) in conjunction with Article 46 paragraph (3) of the ITE Law as the legal basis for imposing imprisonment and fines on defendants who carried out unauthorized electronic information transfer.